Memerankan Disiplin Antropologi Hukum Dalam Penyelesaian Sengketa Agraria - koeswahyono, imam (LPPM Universitas PGRI Adi Buana Surabaya, 2015)
Approach to study of law especially for dispute resolution concerning agrarian resources has been bound on normative positivistic approach